Аdaptness of Personality in the Context of Different Methodological Approaches to the Problem of Adaptation - Reznikova, O. A. (Psychological Prospects Journal, 2011)
In the article the analysis of the concept adaptness is conducted in the context of different methodo-logical approaches to the problem of adaptation, maintenance, varieties of this phenomenon, levels, criteria of its display, is opened the question of the personality conditionality of adaptness. In the completion of the article the conclusion is formulated about harmonious combination in adaptness homoeostatic and heterostatic tendencies in cooperating of a personality with environment.
Keywords: adaptation adaptness levels of adaptness varieties of adaptness personality conditionality of adaptness